2012
DOI: 10.1111/j.1750-3841.2011.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Antioxidant Capacity and Cholinesterase Inhibitory Activity of Citrus aurantifolia Swingle, C. aurantium L., and C. bergamia Risso and Poit. Peel Essential Oils

Abstract: The demonstrated antioxidant activity and procholinesterase properties of Citrus essential oils suggested their use as a new potential source of natural antioxidant to added as extra-nutrient for using in food industries as a valuable new flavor with functional properties for food or nutraceutical products with particular relevance to supplements for the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 38 publications
7
61
0
3
Order By: Relevance
“…Fruit juices of several Citrus cultivars, i.e. C. maxima (shaddock), C. paradisi (grapefruit), C. limon (lemon), C. sinensis (orange) and C. reticulata (tangerine) and the aqueous extracts from C. sinensis, C. paradisi and C. maxima as well as the essential oil isolated from the peels of C. aurantifolia, C. aurantium and C. bergamia were reported to exert selective AChE inhibitory activity varying from moderate to remarkable levels (18,21,22), which seems contrary to our fi ndings on selective BChE inhibition of the Citrus cultivars screened herein (Table 1). Nevertheless, C. limon was reported to have a weak cholinesterase inhibitory activity, dissimilar to most of our data on C. limon cultivars (23).…”
Section: Hptlc Profi Le Of the Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit juices of several Citrus cultivars, i.e. C. maxima (shaddock), C. paradisi (grapefruit), C. limon (lemon), C. sinensis (orange) and C. reticulata (tangerine) and the aqueous extracts from C. sinensis, C. paradisi and C. maxima as well as the essential oil isolated from the peels of C. aurantifolia, C. aurantium and C. bergamia were reported to exert selective AChE inhibitory activity varying from moderate to remarkable levels (18,21,22), which seems contrary to our fi ndings on selective BChE inhibition of the Citrus cultivars screened herein (Table 1). Nevertheless, C. limon was reported to have a weak cholinesterase inhibitory activity, dissimilar to most of our data on C. limon cultivars (23).…”
Section: Hptlc Profi Le Of the Extractsmentioning
confidence: 99%
“…A number of studies have demonstrated a potent cholinesterase inhibitory eff ect of various Citrus species, particularly against AChE, such as C. unshiu (12), C. paradisi (13), C. junos (14), C. medica 'Diamante' (15), C. hystrix (16), C. depressa (17), C. aurantifolia, C. aurantium and C. ber gamia (18)(19)(20), C. maxima, C. paradisi, C. limon, C. sinensis and C. reticulata (21)(22)(23). The health eff ects of Citrus fruits have been principally att ributed to the existence of phenolic compounds including fl avonoids and phenolic acids.…”
Section: Hptlc Profi Le Of the Extractsmentioning
confidence: 99%
“…While this fruit is primarily used in the fragrance industry for its essential oil extracted from its peel, recent studies on the juice from the endocarp of bergamot have shown that it has several bioactivities such as antioxidant, antiinflammatory, cytotoxic, neuroprotective, as well as hypolipidemic and hypoglycemic properties (Currò et al 2016;Impellizzeri et al 2015;Miceli et al 2007;Mollace et al 2008;Risitano et al 2014;Sicari et al 2016;Trovato et al 2010;Tundis et al 2012). From clinical and mechanistic studies, it has been proposed (Mollace et al 2011) that melitidine and brutieridine in concert with naringin and other flavonone glycosides might be responsible for the hypolipidemic effects of BFE and function as do the statin drugs through the direct action on 3-hydroxy-3-methyl-glutaryl -coenzyme A (HMG-CoA) reductase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Overall results showed the dichloromethane extract of S. cryptantha aerial part with the highest anti BChE inhibition at 56.22%, with moderately better antioxidant potential compared to others, it is however not-active against AChE. This suggest that the aerial part of S. cryptantha may contain some considerable amount of Nitrogen [79] and a moderate composition of alkaloidal compounds [80]. Plants products contains a wide variety of bioactive molecules, such as tarpenoids, phenolic, carotenoids, vitamins and other micronutrients which were reported to play vital roles as health protecting agents [81].…”
Section: Discussionmentioning
confidence: 68%